Creativity of an aha! moment and mathematics education - Czarnocha, Bronislaw; Baker, William (Brill/Sense, 2021)
"Creativity of an Aha! Moment and Mathematics Education introduces bisociation, the theory of Aha! moment creativity into mathematics education. It establishes relationships between Koestler's bisociation theory and constructivist learning theories. It lays down the basis for a new theory integrating creativity with learning to describe moments of insight at different levels of student development. The collection illuminates the creativity of the eureka experience in mathematics through different lenses of affect, cognition and conation, theory of attention and constructivist theories of learning, neuroscience and computer creativity. Since Aha! is a common human experience, the book proposes bisociation as the basis of creativity for all. It discusses how to facilitate and assess Aha! creativity in mathematics classrooms. Contributors are: William Baker, Stephen Campbell, Bronislaw Czarnocha, Olen Dias, Gerald Goldin, Peter Liljedahl, John Mason, Benjamin Rott, Edme Soho, Hector Soto, Hannes Stoppel, David Tall, Ron Tzur and Laurel Wolf"--